Two potentially zoonotic parasites infecting Philippine brown deer (Cervus mariannus desmarest, 1822) in Leyte Island (Journal of Advanced Veterinary and Animal Research, 2015)
This  case  report  describes  the  necropsy  findings  of two  potentially  zoonotic  parasites  infecting  the Philippine  brown  deer  (Cervus  mariannus)  in  Leyte Island,  Philippines.  A  female  deer  aging approximately  5-year  was  presented  for  necropsy  to the  Diagnostic  Laboratory  at  the  College  of Veterinary Medicine, Visayas State University. Gross pathology  was  recorded  and  the  selected  organs having  lesion  were  collected  for  histopathological studies. Results showed severe necrotizing lesions in the nasal and palatal areas, infestation of calliphorid maggots,  hepatic  fibrosis,  cholangitis,  cholecystitis, lung atelectasis and duodenitis. Heavy ruminal fluke infection was also observed. Two potentially zoonotic parasites  namely  Fasciola  gigantica  and  Sarcocystis spp.  were  identified.  The  Philippine  brown  deer appears  to  have  a  role  in  transmission  and amplification  of  zoonotic  parasites,  and  can  also  be threatened by diseases caused by the parasites.http://dx.doi.org/10.5455/javar.2015.b110